The march of spare time : the problem and promise of leisure in the Great Depression - Currell, Susan (University of Pennsylvania Press, 2005)
"In The March of Spare Time, Susan Currell explores how and why leisure became an object of such intense interest, concern, and surveillance during the Great Depression. As Americans experienced record high levels of unemployment, leisure was thought by reformers, policy makers, social scientists, medical doctors, labor unions, and even artists to be both a cause of and a solution to society's most entrenched ills. Of all the problems that faced America in the 1930s, only leisure seemed to offer a panacea for the rest." "Currell offers the first full-scale account of the fears and hopes surrounding leisure in the 1930s, one that will be an important addition to the cultural history of the period."--Jacket